2001
DOI: 10.1159/000048837
|View full text |Cite
|
Sign up to set email alerts
|

Dyspepsia Management in Primary Care in The Netherlands: To What Extent Is Helicobacter pylori Diagnosis and Treatment Incorporated?

Abstract: Background: Many guidelines on the management of Helicobacter pylori (HP)-related dyspepsia have been launched over the past decade. The suggested policies in these guidelines are often more consensus- than evidence-based (test-and-treat policy, test and endoscope), which may cause confusion among primary-care physicians. Aim: To determine the current management of HP-related dyspepsia by Dutch general practitioners (GPs). Methods: A random sample of 5% of all Dutch GPs (n = 355) were sent a questionnaire on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…This has led to the development and publication of international and national guidelines that present a unique challenge. The current study, as well as other studies from all over the world, demonstrate only partial adherence of medical communities to these guidelines recommendations [18,19].…”
Section: Discussionsupporting
confidence: 56%
“…This has led to the development and publication of international and national guidelines that present a unique challenge. The current study, as well as other studies from all over the world, demonstrate only partial adherence of medical communities to these guidelines recommendations [18,19].…”
Section: Discussionsupporting
confidence: 56%
“…Dyspepsia and Helicobacter pylori infection are two of the most relevant conditions on digestive-related consultations. [1][2][3] The infection by H. pylori is the most prevalent worldwide, chronically infecting an estimated 50% of the population, 4 a figure similar to that assumed for Spanish population, 5 being the main cause of peptic ulcer and gastric cancer. Over the last decades, the management of H. pylori has migrated from gastroenterology to primary care.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…196, 197 In contrast, educational outreach visits to clinicians and combinations of two or more interventions could increase the likelihood of affecting practice patterns. 196 Some authors have demonstrated that the combination of an educational session led by gastroenterology subspecialists and the availability of office-based H. pylori testing can increase acceptance of the test-and-treat strategy by primary care providers.…”
Section: Implementation Of Guidelines In Clinical Practicementioning
confidence: 99%